Craniofacial fibrous dysplasia: case report of uncommon genetic defect in young adult - Haraziński , Konrad; Goliat, Weronika; Sysło, Oliwia; Jastrzębska, Izabela; Rubik, Nikola; Gmur, Maksym; Gajewski, Michał; Sławińska, Barbara; Błecha, Zuzanna; Maryniak, Nicole (Journal of Education, Health and Sport, 2025)
Fibrous dysplasia is uncommon genetic defect in which normal bone and marrow are replaced with fibro-osseous tissue, leading to bone deformities, pain fractures and functional impairments. The case presents 27 years old women that was diagnosed with sepsis in the course of catheter-related infection and treated at nephrology department. She was diagnosed with chronic kidney disease that started during pregnancy and originated due to steroid-resistant nephrotic syndrome. During the hospitalization, a CT scan of the head was performed because of facial deformation. Based on CT scans of head, craniofacial fibrous dysplasia was confirmed.